Unilateral Hearing Loss Due to Cochlear Nerve Involvement as Isolated Symptom of a Primary Medulloblastoma - Magg, Janine; Nägele, Thomas; Alber, Michael; Weichselbaum, Annette; Ebinger, Martin; Schuhmann, Martin U. (Neuropediatrics, 2020)
Unilateral sensorineural hearing loss is a common symptom of vestibular schwannomas in adolescent patients with neurofibromatosis type 2 or sporadic vestibular schwannomas and is often the initial clinical feature. While rare cases of sensorineural impairment presenting as vision or hearing loss due to metastatic medulloblastoma are known, hearing loss as an isolated presenting symptom of primary malignant neuroepithelial tumors of the central nervous system has not been reported in the pediatric population so far. We present two adolescents with unilateral hearing loss due to cochlear nerve dysfunction as the only symptom of a primary nonmetastatic medulloblastoma of the WNT signaling pathway family members subgroup.
Keywords: unilateral hearing loss; medulloblastoma; MRI